Toes, teeth, and tentacles : a curious counting book - Jenkins, Steve, 1952-2021; Page, Robin, 1957- (Little, Brown and Company, 2025)
"This book highlights the numerous strange and fascinating features and appendages, from teeth to toes to tongues, of all kinds of animals"--